Association of the bacteria Xanthomonas campestris pv. pruni with leaves spot disease in Green Mountin District - Abonesira, Fawzia M.; AlMesmari, Fathi S.; AlDabbgh, Wail Y. (Al-Mukhtar Journal of Sciences, 2003)
A survey conducted during spring 1997 of the diseases effecting stone fruit trees in Green Mountain district, revealed awide spread of leaf spot disease on Almond, Peach, Plum and Apricot trees. Subsequent studies on pathogenicity, morphological and physiobiochemical properties of the causal agent, indicated the association of the bacteria xanthomonas campestris pv. pruni with the disease symptoms. Studies on the host range showed that all isolates of the bacteria were able to infect and produce the typical disease symptoms on the leaves of peach, Amond, Plum, Cherry, Apple and Rose but not on the varity stanley of Plum and Bitter Almond varities. The bacterium was also found to survive the winter season in the flower buds and to retain its infectivity in diseased leave tissues for eight months which consequently provide a source of primary inoculm for spring infection of newly emerging leaves.